Factors that influence the quality of final impressions for fixed dental prostheses in Nairobi, Kenya - Gikunda, Mary K.; Osiro, Olivia A.; Simila, Hazel O.; Alasow, Kassim B.; Nyaga, James M. (International Journal of Dental Materials, 2023)
Background: Good quality dental impressions free of air bubbles, voids, steps, drags, streaks and tears are a pre-requisite for the fabrication of well-fitting fixed dental prostheses (FDP). The quality of impressions is dependent on clinician and material factors.Aim: To evaluate factors that influence the quality of final impressions for FDP in Nairobi, Kenya. Methods: In this cross-sectional study, 234 impressions received by five dental laboratories were analyzed. The study collected information on the type of tray, impression material, technique, type of prostheses, and clinically detectable errors, including voids, inadequate material at margins, tears, steps, drags, and streaks. Impression quality was the outcome assessed as good, fair, or poor by two investigators. The independent variables influencing impression quality included clinician specialty, experience, impression material, technique, and tray type.Results: Inter-rater agreement was 96.8% (p